Zastosowanie komunikacji elektronicznej w mediacjach w administracji publicznej - Tabernacka, Magdalena (Studia Prawa Publicznego, 2018)
In the light of the applicable regulations governing administrative proceedings, electronic communication is an acceptable form of communication between the authority and other parties in the area of activities regulated by the provision of Article 13 of the Act of 14 June 1960, the Code of Administrative Procedure, in its current wording. Since this provision provides for the use of mediation in the resolution of disputes relating to the settlement of matters which are the subject of administrative proceedings in the first and second instance, electronic communication may also be used in mediation at both stages of the administrative proceedings. The mediation process itself may be carried out using Internet means of communication, and the mediator may in the same way contact the body referring the case to mediation. Teleconferencing and other methods of electronic communication, such as e-mails, chat-rooms and teleconferences, are all possible under the current legal framework. However, it is not allowed to conduct automated mediation, i.e. mediation in which identification of a specific mediator will not be possible. In the light of current legislation in force, a mediator must be involved in the supervision of the mediation process and be responsible for its course. This is the personal responsibility of the mediator. The trend to use electronic communication in the public sphere will continue. This will apply both to the communication within the internal structures of the administration and to its external relations. The development of e-administration may also facilitate the development of ADR (Alternative Dispute Resolution) methods in administrative proceedings. This corresponds to the global trend where the methods and procedures of administration are being adopted to the environment which is increasingly using different forms of electronic communication.